Principi contro i totalitarismi e rifondazione costituzionale Volume III - De Siervo, Ugo (Edizione Nazionale delle Opere di Giorgio La Pira, 2019)
- Table of contents - VOLUME I Early period edited by Piero Antonio Carnemolla VOLUME II The Romanistic foundation. Writings on History and Roman law edited by Patrizia Giunti VOLUME III Principles against totalitarianism and constitutional refoundation edited by Ugo De Siervo VOLUME IV The city and the human person. Social, political and administrative texts edited by Pier Luigi Ballini, Giulio Conticelli VOLUME V The construction of peace. International politics texts edited by Bruna Bagnato VOLUME VI The believer and the Church. Texts on religious and ecclesiastical life edited by Bruna Bocchini, Augusto D'Angelo VOLUME VII Indexes of the National Edition of Giorgio La Pira's Works